Decreased influenza activity during the COVID-19 pandemic in Ghana, 2020 - Asante, Ivy Asantewaa; Nyarko, Stephen Ofori; Awuku-Larbi, Yaw; Obeng, Richard Asomadu; Sarpong, Gifty Mawuli; Amenuvor, Esinam Aku Apefa; Adusei-Poku, Mildred; Boatemaa, Linda; Magnusen, Vanessa; Wutsika, Jennifer; Ago, Samuel; Kwasah, Lorreta; et al. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic had a significant effect on influenza activity globally. In this study, we analyzed trends of influenza activity in 2020 during the COVID-19 pandemic in Ghana. Methods This was a cross-sectional study using active prospective influenza surveillance data from 29 sentinel sites. At the sentinel sites, we enrolled patients presenting with symptoms based on the WHO case definition for influenza-like illness (ILI) and severe acute respiratory illness (SARI). Oro and nasopharyngeal swabs were collected from patients and tested for the presence of influenza viruses using specific primers and probes described by the US-CDC. The percentage of positivity for influenza between 2017–2019 and 2021 was compared to 2020. Using the test for proportions in STATA 17.0 we estimated the difference in influenza activities between two periods. Results and discussion Influenza activity occurred in a single wave during the 2020 surveillance season into 2021, September 28 2020–March 7 2021 (week 40, 2020–week 9, 2021). Influenza activity in 2020 was significantly lower compared to previous years (2017– 2019, 2021). Influenza A (H3) was more commonly detected during the early part of the year (December 30, 2019–March 8, 2020), while influenza B Victoria was more commonly detected toward the end of the year (September 28–December 28). In Ghana, adherence to the community mitigation strategies introduced to reduce transmission of SARS-CoV-2, which affected the transmission of other infectious diseases, may have also impacted the transmission of influenza. To the best of our knowledge, this is the first study in Ghana to describe the effect of the COVID-19 pandemic on influenza activity. The continuation and strict adherence to the non-pharmaceutical interventions at the community level can help reduce influenza transmission in subsequent seasons.